Modeling Stock Market Returns of BRICS with a Markov-Switching Dynamic Regression Model - Xaba, Diteboho; Moroke, Ntebogang Dinah; Rapoo, Ishmael (Journal of Economics and Behavioral Studies, 2019)
This article adopted a Markov-switching dynamic regression (MS-DR) model to estimate appropriate models for BRICS countries. The preliminary analysis was done using data from 01/1997 to 01/2017 and to study the movement of 5 stock market returns series. The study further determined if stock market returns exhibit nonlinear relationship or not. The purpose of the study is to measure the switch in returns between two regimes for the five stock market returns, and, secondly, to measure the duration of each regime for all the stock market returns under examination. The results proved the MS-DR model to be useful, with the best fit, to evaluate the characteristics of BRICS countries.